Effect of permafrost thaw on plant and soil fungal community in a boreal forest: Does fungal community change mediate plant productivity response?. (4th March 2019) - Schütte, Ursel M. E.; Henning, Jeremiah A.; Ye, Yuzhen; Bowling, Annie; Ford, James; Genet, Hélène; Waldrop, Mark P.; Turetsky, Merritt R.; White, Jeffrey R.; Bever, James D.
Abstract: Permafrost thaw is leading to rapid shifts in boreal ecosystem function. Permafrost thaw affects soil carbon turnover through changes in soil hydrology; however, the biotic mechanisms regulating plant community response remain elusive. Here, we measured the response of fungal community composition and soil nutrient content in an intact permafrost plateau forest soil and an adjacent thermokarst bog and evaluated their potential to mediate shifts in plant composition. We used barcoded amplicon targeting ITS2 and 28S rRNA genes to determine fungal community composition. Next, we used the soils from the permafrost plateau and the thermokarst bog as soil inoculum in a greenhouse experiment to measure whether shifts in fungal community and soil water level regulate plant productivity and composition. Overall, we found that fungal community composition differed significantly between the thawed and intact permafrost sites, but soil nutrient content did not. Relative abundance of mycorrhizal fungal taxa decreased while relative abundance of putative fungal pathogens increased with permafrost thaw. In the greenhouse, we found that ecto‐ and arbuscular‐associated host plants had higher productivity in permafrost‐intact soils relative to thawed soils. However, productivity of non‐mycorrhizal tussock grass was more affected by soil water levels than soil communities. Synthesis. Our results suggest that fungal communities are crucial in mediating plant community response to permafrost thaws inducing hydrology changes. Abstract : Our results suggest that fungal communities are crucial in mediating plant community response to permafrost thaws inducing hydrology changes.